National culture and international business: A path forward - Shenkar, Oded; Tallman, Stephen B; Wang, Hao; Wu, Jie (Journal of International Business Studies, 2022)
The anniversary of Kogut and Singh’s construct of “cultural distance” is a good time to reflect on this immensely popular but flawed construct, assess the efficacy of the remedies offered for its reform and refinement, and chart an alternative approach that represents a departure from distance as the dominant paradigm with which to view and analyze the impact of national culture on cross-border business. The proposed alternative, a contact-based framework shifts attention from what sets cultures apart towards the actual cultural interface that firms and their executives experience when participating in an international transaction. With this lens, the cultural exchange is regarded as an evolving interactional process of engagement, which commences prior to a transaction and proceeds through the life of the inter-party arrangement and beyond, and whose potential to yield negative – or positive – outcome is subject to specific contingencies. Implications for theory, methodology, and practice are delineated.